Puzzle Facelift: A Nonsurgical, Whole Treatment for Facial Modeling and Rejuvenation - Bertossi, Dario; Nocini, Riccardo; Chirumbolo, Salvatore; Kapoor, Krishan Mohan (Facial Plastic Surgery, 2022)
The assessment of correct anatomy of face and the evaluation of the dynamic interplay between anatomy and function, to get an overall improvement, is a leading topic in aesthetic surgery and has increased its impact in recent years. A nonsurgical impact technique reduces both post-treatment discomfort and the overall cost. Obtaining the simultaneous correction in forehead, nose, lips, and chin means obtaining an overall improvement in face view. Likewise, the high predictability of the procedure and the absence of alloplastic implant, bone re-absorption, and scars have to be considered in nonsurgical aesthetic medicine. In conclusion, a single session of profile correction using hyaluronic acid filler should be proposed to patients, every time the aesthetic practitioner sees a coexistence of forehead, nose lips, and chin defects.
Keywords: face puzzle; aesthetics; whole facial treatments; dynamics; alloplastic implants